Verifikasi Keaslian Tugas Sekolah Berdasarkan Analisis Tulisan Tangan Menggunakan Kombinasi Convolutional Neural Network Dan Siamese Network - Rahayu, Indah; Hutagulung, Fatma Sari (Lembaga Riset Mutiara Akbar, 2025)
The authenticity of school assignments is crucial for maintaining the objectivity of learning evaluations. However, the practice of having assignments submitted by third parties is still common. This study develops an assignment authenticity verification system based on handwriting analysis using image processing and machine learning approaches. This system utilizes a Convolutional Neural Network (CNN) for visual feature extraction and a Siamese network to measure handwriting similarity. The data used includes the writing of sixth-grade students at SD Negeri 060868 Medan Timur and writing from non-students as comparisons. The handwriting images were converted to grayscale, resized to 128x128 pixels, and then processed to generate a one-dimensional feature vector. A similarity score was calculated using Euclidean distance, and if the value is ? 0.75, it is considered a match. This system was built with Python, TensorFlow, and OpenCV, and integrated into web and mobile platforms. Trial results show that the system is capable of automatically verifying assignment authenticity, helping teachers assess more objectively and efficiently, and improving academic transparency.